Ceratozetes (Ceratozetes) colchicus Murvanidze & Weigmann 2003 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Ceratozetes (Ceratozetes) colchicus Murvanidze & Weigmann, 2003 * Material – New record for Turkey. One specimen in Alasökü Village, Taşköprü forest, N 41° 19′ 55.68′′, E 34° 25′ 16.18′′, alt. = 1369 m, 16 June 2018, tree trunk of P. sylvestris; one specimen in Şahinler Natural park, Ankara. N 40° 61′ 74.65′′, E 32° 45′ 55.46′′, alt. = 1670 m, 16 June 2018, soil. Global distribution – Caucasus and Turkey. Ecology – Humid forest soils. Remarks – Measurements: Body size: 500 × 320 µm. ro 65 µm, in 130 µm, le 75 µm, ss 95 µm, ng vestigial. Turkish specimens show smaller size compared to the original description (Murvanidze and Weigmann 2003): 1) body length in Turkish specimens is about 500–510 µm, while in description 540–580 μm is indicated; 2) lamellar setae 75 μm vs reported 85 µm; 3) ss 95 µm vs 150 µm; 4) length of lamellar cuspides 50 µm vs 80 µm. The rest of the characters match the provided description and paratypes available in the collection of the Georgian Agricultural University.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 267, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Ceratozetes colchicus; Arachnida; Ceratozetidae; Animalia; Biodiversity; Sarcoptiformes; Ceratozetes; Taxonomy; 15. Life on land